MINERAL AND PHYSICAL AND CHEMICAL CHANGES IN MAGNETITE QUARTITES OF THE VALYAVKINSKY AND NOVOKRIVORIZKY DEPOSITS OF THE KRYVBUS DURING THEIR MINERAL PROCESSING - НUBINA Viktoriia; VERKHOVTSEV, Valentyn; YATSENKO, Viktor; POKALYUK, Volodumyr; ZABOROVSKA, Larysa; LAVRYNENKO, Olena; LYTVYNENKO, Yuriy (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. In order to study the mineral physical and chemical changes that occur with iron ore (magnetite quartzites) of the Valyavkinsky and Novokrivorizky deposits of the Kryvorizka iron ore basin during the mining and processing of ore at the mining and processing plant "ArcelorMittal Kryvyi Rih", the entire technological chain of mining and mineral processing was analyzed: magnetite quartzite (ore) in naturaldeposits → ore after explosion → ore after crushing at crushing plants → intermediate magnetic products and tailings of all stages of beneficiation → final magnetite concentrate. Methods. Laboratory and analytical studies, which include mineragraphic, petrographic, electron microscopic studies of iron ore, X-ray fluorescence method and atomic emission spectral analysis (determination of the content of macro- and microelements in the original ore, magnetic concentrate and tailings), X-ray diffraction analysis, microprobe analysis of magnetic concentrate and tailings, thermogravimetric analysis, chromatographic method (determination of the specific surface of a substance), sedimentation analysis, measurement of magnetic characteristics, etc. were used. Results. It was established that at the first stage of mining production (drilling and blasting, ore crushing in the quarry and at the crushing plant) there are no significant changes in minerals. At the next stage of deep processing and concentration of minerals at the ore beneficiation plant, during which the ore undergoes 3 stages of crushing, classification, desliming, and wet magnetic separation, two completely new products are formed – magnetite concentrate and tailings, which are fundamentally different from the original ore – both at the rock level and at the mineral one. Сonclusions. It was substantiated that in the process of enrichment of magnetite quartzites, the structural and textural characteristics, mineral and chemical composition, state of aggregation of the iron ore, structural and crystallochemical properties of the main ore mineral magnetite change significantly.